2009
DOI: 10.1007/s00167-009-0842-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bone marrow edema size and knee pain

Abstract: The purpose of our study was to determine the changes in the size of the edema observed on MRI scans and its relation to the activity pain of the patient and the rest pain in bone marrow edema (BME). A total of 51 patients were followed up at 3-month intervals for a period of 1 year. During the follow-ups, MRI scans of the patients' knees were obtained; the scores obtained on the Stanmore functional rating scale and visual analog scale were determined. The changes in these parameters and the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Although the BME area on MRI scans had not disappeared in all cases, the functional results were all good or excellent. It has been reported that the BME area is not necessarily correlated to pain [ 22 ], and that MRI abnormalities may take up to 16 months before resolving [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the BME area on MRI scans had not disappeared in all cases, the functional results were all good or excellent. It has been reported that the BME area is not necessarily correlated to pain [ 22 ], and that MRI abnormalities may take up to 16 months before resolving [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the type 1 (oedema type) group tended to have a larger effect. More bone marrow oedema may be associated with worse pain and disability [22][23][24] and might indicate more severe disease with a larger potential for improvement. Therefore, we hypothesised a larger effect of amoxicillin in subgroups with more versus less MC-related oedema.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 For BME size and knee pain, Unay et al found a weak but significant correlation for the Stanmore Functional Rating Scale (SFRS) (r = 0.313, P = .025) but no correlation for the VAS (r = 0.203, P = .153). 31 Tonbul et al reported on idiopathic BME of the talus, showing a poor correlation to the AOFAS scores (r = 0.313, P = .025) and no correlation to the VAS (r = 0.203, P = .153). 30 These consistent findings raise the question on where the residual pain originates from.…”
Section: Discussionmentioning
confidence: 99%